HIGH DISCIPLINE IS THE WINNING FACTOR - A.R. Shoxakimov (Web of Journals Publishing, 2024)
The article presents thoughts and opinions on the issues of studying the historical roots of our national heritage, promoting the exemplary life of our great ancestors, ensuring high military discipline in military society.
Keywords: Military discipline, combat effectiveness, fighting spirit, daily activities, courage, self-sacrifice, discipline, cyber terrorism, national spirit, military comradeship, discipline mechanism.